MicroRNAs regulating macrophages infected with Leishmania L. (V.) Braziliensis isolated from different clinical forms of American tegumentary leishmaniasis - Lago, Tainã; Medina, Lilian; Lago, Jamile; Santana, Nadja; Cardoso, Thiago; Rocha, Alan; Leal-Calvo, Thyago; Carvalho, Edgar M.; Castellucci, Léa Cristina (Frontiers in Immunology, 2023)
Background Leishmaniasis is an infectious disease caused by protozoa of the genus Leishmania. There are still no vaccines, and therapeutic options are limited, indicating the constant need to understand the fine mechanisms of its pathophysiology. An approach that has been explored in leishmaniasis is the participation of microRNAs (miRNAs), a class of small non-coding RNAs that act, in most cases, to repress gene expression. miRNAs play a role in the complex and plastic interaction between the host and pathogens, either as part of the host’s immune response to neutralize infection or as a molecular strategy employed by the pathogen to modulate host pathways to its own benefit. Methods Monocyte-derived macrophages from healthy subjects were infected with isolates of three clinical forms of L. braziliensis: cutaneous (CL), mucosal (ML), and disseminated (DL) leishmaniasis. We compared the expression of miRNAs that take part in the TLR/NFkB pathways. Correlations with parasite load as well as immune parameters were analyzed. Results miRNAs -103a-3p, -21-3p, 125a-3p -155-5p, -146a-5p, -132- 5p, and -147a were differentially expressed in the metastatic ML and DL forms, and there was a direct correlation between miRNAs -103a-3p, -21-3p, -155-5p, -146a-5p, -132-5p, and -9-3p and parasite load with ML and DL isolates. We also found a correlation between the expression of miR-21-3p and miR-146a-5p with the antiapoptotic gene BCL2 and the increase of viable cells, whereas miR-147a was indirectly correlated with CXCL-9 levels. Conclusion The expression of miRNAs is strongly correlated with the parasite load and the inflammatory response, suggesting the participation of these molecules in the pathogenesis of the different clinical forms of L. braziliensis.